Pelaksanaan Program Pengembangan Karir Pada Anak Berkebutuhan Khusus di Surakarta - Itsna Safira; Galih Fajar Fadillah; Farah Nilawati (Scidacplus, 2023)
This study aims to describe how the implementation of career development in improving career planning in children with special needs. The research method used is qualitative with a case study approach to describe a case completely and thoroughly in order to obtain more detailed and in-depth information. The selection of subjects in this study used purposive sampling techniques, namely two vocational teachers, one teacher member of the Special Job Fair. Data collection techniques with interviews, observation, and documentation. The findings of the study showed that career development services provided include orientation services, information services, and placement services. The delivery methods used are lectures, demonstrations, assignments, and training. Then the career planning aspect is shown through career understanding, finding information, as well as planning and decision making. While factors that influence career planning include environmental conditions and family support, learning experiences, and task coping skills.